Pengaruh Green Accounting, Tanggung Jawab Lingkungan, Gender Diversity, Media Exposure, Slack Resources Terhadap Pengungkapan Corporate Social Responsibility (CSR) - Galuh Candra Kirana; Rina Trisnawati (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study aims to analyze the effect of green accounting, environmental responsibility, gender diversity, media exposure, and slack resources on Corporate Social Responsibility (CSR) disclosure in food and beverage sector companies listed on the (IDX) for the period 2019–2023. The sampling technique used the purposive sampling method and obtained 15 companies. With a total final sample of 55. The research method used is quantitative, with secondary data obtained from the company's annual report. Data analysis was carried out using multiple linear regression with the help of the SPSS 25 program. The results of the study showed that only media exposure had a significant positive effect on CSR disclosure, while green accounting, environmental responsibility, gender diversity, and slack resources did not have a significant effect on CSR disclosure.